Invasive Mold Infections in Solid Organ Transplant Recipients - Yoann Crabol; Olivier Lortholary (Scientifica)
Invasive mold infections represent an increasing source of morbidity and mortality in solid organ transplant recipients. Whereas there is a large literature regarding invasive molds infections in hematopoietic stem cell transplants, data in solid organ transplants are scarcer. In this comprehensive review, we focused on invasive mold infection in the specific population of solid organ transplant. We highlighted epidemiology and specific risk factors for these infections and we assessed the main clinical and imaging findings by fungi and by type of solid organ transplant. Finally, we attempted to summarize the diagnostic strategy for detection of these fungi and tried to give an overview of the current prophylaxis treatments and outcomes of these infections in solid organ transplant recipients.